ISOLASI SELULOSA MESOCARP KULIT DURIAN UNTUK BAHAN BAKU PEMBUATAN BIOFOAM - Suryaningsih, Wahyu; Budiati, Titik; Muspita Dyah Utami , Merry; Ardhiarisca, Oryza; Candra Dewi, Aryanti (Politeknik Negeri Jember, 2025)
The high potential of durian fruit creates waste in the form of skins that cause environmental pollution. Durian peel contains high cellulose of about 50 to 60%. Therefore, it is necessary to explore the source of cellulose as raw material for cheap bioplastic and biodegradable foam packaging. This study aims to determine the physical and chemical properties of durian peel mesocarp cellulose. The research method was to isolate or extract cellulose from durian peel mesocarp. The cellulose isolation process consists of 3 stages, namely flour making, delignification process using 10% NaOH alkaline solution, and bleaching process using 10% hydrogen peroxide (H2O2) solution. The cellulose produced was observed for physical and chemical properties. The results show that durian peel mesocarp cellulose has physical properties with powder form, elongated round granule structure, yellowish-white color with lightness (L) = 78.50, a * = 4.30, and b * = 21.00, and chemical properties include moisture content of 6.37%, content of 63.27% cellulose, 13.94% hemicellulose and 9.54% lignin.